PROBLEMATIKA VALIDASI BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN ATAS TEMUAN HASIL VERIFIKASI LAPANGAN NILAI BANGUNAN TIDAK SESUAI DENGAN NILAI JUAL OBJEK PAJAK DAN NILAI PEROLEHAN OBJEK PAJAK - Bonus Aprianto Hernanda (CALYPTRA, 2014)
Tax is the largest revenue for the State of Indonesia. One source of taxes received by the state is Bea Acquisition of Land and Building (BPHTB) which is now submitted to the government to be managed for the benefits of the area. The legal basis is the collection BPHTB Law Number 28 Year 2009 on Regional Taxes and Levies as a substitute for the Act No. 20 of 2000 on the Amendment of the Act No. 21 of 1997. Harvesting BPHTB in Surabaya since 2011 was taken over by the Revenue Office in Surabaya (Revenue’s Surabaya), but in the implementation collection BPHTB by Revenue’s Surabaya there are problems, one of which concerns the validation of the findings BPHTB field verification does not match the value of the building with the Tax Object Sale Value (SVTO/NJOP) listed in the acquisition SPPT and Object Acquisition Value Tax. This study aims to determine the application of collection BPHTB by Revenue’s Surabaya whether in accordance with the Regional Regulation of Surabaya No. 11 Year 2010 concerns BPHTB. This research is a law with legislative approach, the conceptual approach and the historical approach. While the legal materials used are primary legal materials, secondary and tertiary to analyze the existing problems in the implementation of the Regional Regulation of Surabaya No. 11 Year 2010 concerns BPHTB. From the results of this study concluded that the act of Revenue’s Surabaya related to collection BPHTB terms of the application of the Regional Regulation of Surabaya No. 11 Year 2010 concerns BPHTB not appropriate because the Revenue’s Surabaya has not been prepared to take over about collection BPHTB so that the service charges BPHTB becomes chaotic, lack of knowledge Revenue officers in Surabaya about taxation, particularly BPHTB and extent of the region resulted in insufficient numbers of Revenue officers in Surabaya in serving the verification and validation process so that the file be piling up. This resulted in the registration of land rights or registration of transfer of land rights to be obstructed so PPAT cannot carry out their duties in accordance with the legislation in force.